Literature Study: Factors Affecting the Implementation of Hospital Management Information Systems in Hospital - Puguh Ika Listyorini; Athipach Dader; Muhammad Zia Ulhaq; Alifah Sari Nugraini (Global Health Science Group, 2022)
Evaluation of information systems aims to explore and find out, about the extent of an information system implementation activity, both from the point of view of user perception, organization, and information system technology. The purpose of this study is to describe a review of the application of the registration information system in hospitals using the Hot-Fit Method. Human component; shortage of experts, officers who do not understand and understand, the process of inputting patient data is not appropriate or incomplete, negligent officers and officers have not attended training on Hospital Management Information Systems. organizational components; there are still some organizations that are not appropriate such as support, supervision, development from the management is lacking or non-existent, there is no reward, there is no evaluation and Standard Operating Procedure in the implementation of Hospital Management Information System. Technology components; some have not run smoothly, the quality of the system is still found obstacles such as the availability of infrastructure that is not yet appropriate, errors still occur in the system, problematic networks, the quality of information that does not meet expectations and the quality of service that has not been maximized.